2020
DOI: 10.1101/2020.07.03.187138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetics inSinorhizobium melilotienables spatial control of exopolysaccharide production and biofilm structure

Abstract: AbstractMicroorganisms play a vital role in shaping the soil environment and enhancing plant growth by interacting with plant root systems. Due to the vast diversity of cell types involved, combined with dynamic and spatial heterogeneity, identifying the causal contribution of a defined factor, such as a microbial exopolysaccharide (EPS), remains elusive. Synthetic approaches that enable orthogonal control of microbial pathways are a promising means to dissect such complexity. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…To extend the techniques described in this article to mixed-kingdom communities, optogenetic systems developed for bacteria ( 73 , 74 ) could be utilized. Indeed, in Sinorhizobium meliloti , a nitrogen-fixing soil bacterium, the blue light-sensitive transcription factor EL222 was recently used to control production of the public good exopolysaccharide, enabling manipulation of biofilm formation ( 41 ). Hybrid optochemical approaches also hold promise for repurposing existing inducible systems, as a recent study showed that photocaged isopropyl-β- d -thiogalactopyranoside (IPTG) could be used to control coculture interactions in the bacterium Corynebacterium glutamicum ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend the techniques described in this article to mixed-kingdom communities, optogenetic systems developed for bacteria ( 73 , 74 ) could be utilized. Indeed, in Sinorhizobium meliloti , a nitrogen-fixing soil bacterium, the blue light-sensitive transcription factor EL222 was recently used to control production of the public good exopolysaccharide, enabling manipulation of biofilm formation ( 41 ). Hybrid optochemical approaches also hold promise for repurposing existing inducible systems, as a recent study showed that photocaged isopropyl-β- d -thiogalactopyranoside (IPTG) could be used to control coculture interactions in the bacterium Corynebacterium glutamicum ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Light is a powerful actuator, as it is inexpensive, easily controlled in time and space, and S. cerevisiae contains no known native photoreceptors ( 34 ). Light can be rapidly added and removed from cell cultures or spatially targeted ( 35 38 ), meaning it can be used to study how regulation of microbial interactions determines microbial community development ( 39 41 ). We report here the development of an optogenetic tool that allows the expression of a specific metabolic enzyme of interest to be put under light control in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%
“…To extend the techniques described in this article to mixed-kingdom communities, optogenetic systems developed for bacteria 80,81 could be utilized. Indeed in Sinorhizobium meliloti , a nitrogen fixing soil bacterium, the blue-light sensitive transcription factor EL222 was recently used to control production of the public good exopolysaccharide enabling manipulation of biofilm formation 41 . Hybrid optochemical approaches also hold promise for repurposing existing inducible systems, as a recent study showed that photocaged IPTG could be used to control coculture interactions in the bacterium Corynebacterium glutamicum 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Light is a powerful actuator as it is inexpensive, easily controlled in time and space, and S. cerevisiae contains no known native photoreceptors 34 . Light can be rapidly added and removed from cell cultures or spatially targeted 3538 , meaning it can be used to study how regulation of microbial interactions determines microbial community development 3941 . We report here the development of an optogenetic tool that allows the expression of a specific metabolic enzyme of interest to be put under light control in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%